Arthroscopic Meniscal Root Repair Using a Ceterix NovoStitch Suture Passer - Andrew J. Blackman, M.D.; Michael J. Stuart, M.D.; Bruce A. Levy, M.D.; Mark A. McCarthy, M.D.; Aaron J. Krych, M.D. (Arthroscopy Techniques, 2014)
Meniscal root injuries can compromise knee function and lead to early degenerative changes if not appropriately treated. Numerous techniques have been described; however, the technical difficulties in performing these repairs are well known. Furthermore, the relative strengths of various repair techniques have been examined. This article describes a single–working portal meniscal root repair technique using a double-locking loop suture configuration with a novel suture-passing device that offers a strong, reproducible repair construct.